amorphous wrote:

If a + b = 20, then (a + b/2) + (b + a/2) =

A) 10

B) 20

C) 30

D) 40

E) 50

Here's another approach:

GOAL: find the value of (a + b/2) + (b + a/2)

GIVEN: a + b = 20

Let's take some values of a and b that satisfy the equation a+b = 20, and plug them into our goal expression...

Well, a =

20 and b =

0 satisfy the equation a + b = 20

Now take (a + b/2) + (b + a/2), and replace a and b with

20 and b =

0We get: (a + b/2) + (b + a/2) = (

20 +

0/2) + (

0 +

20/2)

= (20 + 0) + (0 + 10)

= 20 + 10

= 30

Answer: C

Cheers,

Brent

_________________

Brent Hanneson – Creator of greenlighttestprep.com

Sign up for my free GRE Question of the Day emails